Continuing teacher training and the teaching of Mathematics in the Salesian School Network of Cuiabá (Research, Society and Development, 2022)
The article highlights the reflections on the experience lived during the professional performance in the Initial Years of the Salesian Network of Cuiabá, from 2005 to 2017. The research aimed to socialize the process of continuing education of teachers of the Salesian Network of Schools, considering the contributions to the teaching and learning process in Mathematics. Descriptive bibliographic research focuses on a qualitative methodological approach, based on systematic and empirical investigation through experience reports. The analyzed data make it possible to infer about the conception of the process of continuous formation of the Salesian network destined to the teachers of the Initial Years; analyze the curricular proposal and the contributions to the teaching and learning process of Mathematics; identify the teaching knowledge acquired by the teachers. In the analyses, it was possible to identify the pedagogical practice, the contents worked and methodological procedures adopted by the Salesiana network for the teaching of mathematics in the Initial Years.